2017
DOI: 10.3390/cryst8010003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crystal Orientation on the Crack Propagation of Sapphire by Sequential Indentation Testing

Abstract: Single-crystal sapphire (α-Al 2 O 3) is a hard and brittle material. Due to its highly crystalline nature, the fracture behavior of sapphire is strongly related to its crystal structure, and understanding the effects of crystal structure on the crack propagation of sapphire is essential for the successful application of this important material (e.g., as wafers in the electronics industry). In the present work, crack propagation that is induced by sequential indentation was investigated on the A-plane and C-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…O 3 -Cr 7 C 3 interface, and 3.55 MPa √ m for the Cr 7 C 3 -Cr 2 AlC interface. In comparison, single crystal alumina when measured by indentation cracking[49] is around 1.5 MPa √ m, very similar to that of the alumina-based interface. Hirota measures, in a 97% Cr 7 C 3 -3% Cr 2 O 3 sample, a fracture toughness of[12], it is promising to see that without any design or im-provement of the interfaces, they are nevertheless in line with typical literature values.…”
mentioning
confidence: 54%
“…O 3 -Cr 7 C 3 interface, and 3.55 MPa √ m for the Cr 7 C 3 -Cr 2 AlC interface. In comparison, single crystal alumina when measured by indentation cracking[49] is around 1.5 MPa √ m, very similar to that of the alumina-based interface. Hirota measures, in a 97% Cr 7 C 3 -3% Cr 2 O 3 sample, a fracture toughness of[12], it is promising to see that without any design or im-provement of the interfaces, they are nevertheless in line with typical literature values.…”
mentioning
confidence: 54%
“…When the indenter was indented to enough depth of the specimen, the stress is transmitted from the apex of indenter to the specimen. It was reported that the stress was concentrated along the ridge line of the indenter [14]. Therefore, if the ridge line of indenter was oriented to m -axis, the stress was concentrated to the fragile m -axis, and eventually the hardness along m -axis became low.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that during nanoindentation experiments, when using non-spherical indenters, the deformation and crack patterns are not only dependent on the crystallography of the sample, but it is also influenced by the tip geometry; e.g. cracks always start at the tip edges due to stress concentration at these locations [22]. Hence, spherical indenters were chosen to avoid the influence of the tip geometry in the stress distribution on the sample during the test and so to measure the true deformation and fracture behavior of sapphire.…”
Section: Methodsmentioning
confidence: 99%